ABSORBSI GLUKOSA DAN SUKROSA SEBAGAI SUMBER KARBON UTAMA OLEH KOMUNITAS MPG PADA KONDISI ANAEROBIK-AEROBIK - Supriyati, Dyah (Research Center for Biology-Indonesian Institute of Sciences, 2009)
To study the role of substrate on the establishment of glycogen accumulating organism (MPG), activated sludge originated from anaerobic-aerobic process was implemented on waste water treatment plant which was acclimated with glucose and sucrose.Both susbtrates were effectively utilized by microbial communities during anaerobic condition. Those absorbed substances were converted to glycogen.Glycogen was also used as energy generating process as indicated by a decrease of glycogen. The dominancy of glycogen accumulating organism suppresses the polyphosphate accumulating organism as indicated by no significant release of orthosphosphate during anaerobic condition.